Observing wildlife through the eyes of Nils Lindahl Elliot - Mäekivi, Nelly; Rattasepp, Silver (Sign Systems Studies, 2020)
Review of Observing Wildlife in Tropical Forests. 1: A Geosemeiotic Approach by Nils Lindahl Elliot. Bristol: Delome Publications, 2019, 480 pp.